This present darkness eaudiobook This present darkness series, book 1. - Peretti, Frank E. (This Present Darkness, 2010)
Ashton is just a typical small town. But when a skeptical reporter and a prayerful pastor begin to compare notes, they suddenly find themselves fighting a hideous New Age plot to subjugate the townspeople, and eventually the entire human race.